Fair Representation : Meeting the Ideal of One Man, One Vote - Balinski, Michel L. (Book collections on Project MUSE., 2010)
The issue of fair representation will take center stage as U.S. congressional districts are reapportioned based on the 2000 Census. Using U.S. history as a guide, the authors develop a theory of fair representation that establishes various principles for translating state populations#x97;or vote totals of parties#x97;into a fair allocation of congressional seats. They conclude that the current apportionment formula cheats the larger states in favor of the smaller, contrary to the intentions of the founding fathers and compromising the Supreme Court's ""one man, one vote"" rulings. Balinski and Young i.